A meta‐analysis of the differential relations of traditional and cyber‐victimization with internalizing problems. Issue 2 (21st November 2017) - Gini, Gianluca; Card, Noel A.; Pozzoli, Tiziana
Abstract : This meta‐analysis examined the associations between cyber‐victimization and internalizing problems controlling for the occurrence of traditional victimization. Twenty independent samples with a total of 90, 877 participants were included. Results confirmed the significant intercorrelation between traditional and cyber‐victimization ( r  = .43). They both have medium‐to‐large bivariate correlations with internalizing problems. Traditional victimization ( sr  = .22) and cyber‐victimization ( sr  = .12) were also uniquely related to internalizing problems. The difference in the relations between each type of victimization and internalizing problems was small (differential d  = .06) and not statistically significant ( p  = .053). Moderation of these effect sizes by sample characteristics (e.g., age and proportion of girls) and study features (e.g., whether a definition of bullying was provided to participants and the time frame used as reference) was investigated. Results are discussed within the extant literature on cyber‐aggression and cyber‐victimization and future directions are proposed.